Influence Employee Engagement and Self-Efficacy on the Performance of Proklamasi 45 University Employees - Naufa Setyowati; Niken Widyastuti; Diana Anggraini Kusumawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study is to ascertain how Proclamation 45 University's employee performance is impacted by employee engagement and self-efficacy. 57 employees were surveyed for this study. Multiple regression analysis was employed in this investigation. Make use of 0.05 as a valid value. The multiple regression equation, Y = -0.419 + 0.496X1 + 0.257 Proclamation 45 University, is derived from the computation and analysis of the data used. It is possible to draw the following conclusions from the above findings. (1) Procrik 45 Employee performance in higher education is positively impacted by employee engagement. This implies that improved employee performance will follow from high employee engagement. (2) Employee performance and self-efficacy are positively impacted by Proklamasi 45 University. This implies that employee performance will be even higher when self-efficacy is high. (3) At Proklik 45 University, employee performance is positively impacted by self-efficacy and employee engagement. This implies that when self-efficacy and employee engagement are high, employee performance will likewise be high. It is anticipated that Universitas Proklamasi 45 will keep working to raise employee self-efficacy and engagement in order to raise employee performance.